Effects of cold atmospheric plasma pre-treatment on maintaining the quality of ready-to-eat drunken red shrimp (Solenocera crassicornis) stored at chilled conditions - Yingru Wu; Qiongjing Wu; Huimin Lin; Jie Pang; Xiaomin Zhou; Bin Zhang (Food Chemistry: X, 2023)
This present study investigated the effect of cold atmospheric plasma (CAP) pre-treatment on the quality of ready-to-eat drunken red shrimp (Solenocera crassicornis) during chilled storage. The shrimp were pre-treated with the CAP at 40 kV and 36 kH for 100 s in a plasma generating equipment before the drunken treatment and compared with an untreated control sample. The results showed that the CAP pre-treatment significantly inhibited the total viable count (TVC) values, total volatile basic nitrogen (TVB-N) content, and polyphenol oxidase (PPO) activity of the drunken shrimp compared to the control treatment. Furthermore, the CAP pre-treatment also significantly maintained the myofibrillar protein (MP) content, texture properties, and a more stable histological structure of muscle fibers compared to the control. High-throughput sequencing results confirmed that the CAP pre-treatment significantly reduced the diversity and abundance of several bacteria in the shrimp. Gas chromatography-ion mobility spectrometry (GC-IMS) analysis detected that the CAP pre-treatment effectively maintained the stability of volatile organic compounds (VOCs). These findings provide valuable theoretical support for the processing and storage of drunken shrimp.